2018
DOI: 10.1007/s11469-017-9866-4
|View full text |Cite
|
Sign up to set email alerts
|

Counselor and Drug Detox Inpatient Verbal Behaviors in a Single Session of Motivational Interviewing and Subsequent Substance Use-Related Patient Outcomes

Abstract: Effects of counselor and client verbal behaviors, in a single motivational interviewing (MI) session during inpatient detoxification, were evaluated in relation to 17 study participants' self-reported drug use 3 months later. Also, counselor-to-client transitions in the single MI session were explored for 24 participants, using the Motivational Interviewing Sequential Code for Observing Process Exchanges (MI-SCOPE) coding instrument. Surprisingly, counselor neutral/double-sided reflections predicted lower leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…Thirty studies reported outcomes related to relapse/drug use at follow‐up using a variety of 20 self‐report and 12 objective measures. Self‐reported measures included interviews such as the Interview for Research on Addictive Behaviour [ 60 ] and self‐administered questionnaires such as the Alcohol Use Disorders Identification Test [ 26 , 61 ], Drug Use Disorders Identification Test and the Drug Use Disorders Identification Test‐Extended E [ 62 ], the Cannabis Problems Questionnaire and the Short Form‐12 [ 56 ] and the Severity of Dependence Scale [ 56 , 63 ]. Assessments took place at different intervals, ranging from 2 weeks [ 14 , 24 , 56 ] to 3 years after discharge [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty studies reported outcomes related to relapse/drug use at follow‐up using a variety of 20 self‐report and 12 objective measures. Self‐reported measures included interviews such as the Interview for Research on Addictive Behaviour [ 60 ] and self‐administered questionnaires such as the Alcohol Use Disorders Identification Test [ 26 , 61 ], Drug Use Disorders Identification Test and the Drug Use Disorders Identification Test‐Extended E [ 62 ], the Cannabis Problems Questionnaire and the Short Form‐12 [ 56 ] and the Severity of Dependence Scale [ 56 , 63 ]. Assessments took place at different intervals, ranging from 2 weeks [ 14 , 24 , 56 ] to 3 years after discharge [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies reported outcomes related to self‐efficacy. Self‐report measures used were the 12‐item versions of the Alcohol Abstinence Self‐Efficacy Scale and Drug Abstinence Self‐Efficacy Scale in one study [ 62 ] and the Brief Situational Confidence Questionnaire in another [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Also, the interaction of client and therapist behaviors (i.e. sequential analysis) has been studied using MI concepts ( Apodaca et al, 2016 ; Berman et al, 2019 ; Drage et al, 2019 ; Laws et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%